Expert System for Diagnosing Chicken Diseases using Bayes' Theorem - Monica Angriani Br. Simatupang (Institute of Computer Science, 2020)
Chicken disease is a condition in which the organs of the chicken farm cannot function normally. To make a diagnosis of the disease requires further examination carried out by specialists (experts). An expert system is a system that uses human knowledge entered into a computer to solve problems that are usually solved by experts. The system created in solving the problem uses the Bayes theorem method where the inference process uses Forward Chaining. The application was developed using the Visual Basic 2010 programming language and MySQL database.